2019
DOI: 10.1186/s40807-019-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solvents on the extraction and purification of vegetable dyes onto the efficiency for dye-sensitized solar cells

Abstract: Eight vegetable dyes extracted from flowers, fruits and leaves abundant in the wide biodiversity of the Andes region of South America were extracted with ethanol without purification to explore as vegetable photosensitizers in dye-sensitized solar cells (DSSCs). The absorbance spectra were measured by UV-visible spectroscopy and the photoelectrical performance of the DSSCs based on these dyes with a homemade solar simulator, constructed only for educational purposes under 1 sun of illumination. The open-circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Consequently, the results obtained using anthocyanins are lower or comparable to those reported in other studies: Rhuc/sumas fruits (1.5%) [25], Hibiscus sabdariffa (0.033%) [15], Brassica olercea (0.13%) [26]. The performance of the fabricated devices may be affected by the type of absorption between the anthocyanins and the TiO 2 pore structure [24]. It is assumed that the similarity in size between the pores and dye molecules results in more adsorption until the pores are filled with anthocyanins.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Consequently, the results obtained using anthocyanins are lower or comparable to those reported in other studies: Rhuc/sumas fruits (1.5%) [25], Hibiscus sabdariffa (0.033%) [15], Brassica olercea (0.13%) [26]. The performance of the fabricated devices may be affected by the type of absorption between the anthocyanins and the TiO 2 pore structure [24]. It is assumed that the similarity in size between the pores and dye molecules results in more adsorption until the pores are filled with anthocyanins.…”
Section: Resultsmentioning
confidence: 48%
“…Consequently, the leaves purified extract exhibits a higher absorbance compared to the other extracts which can be linked to the presence of high concentration of anthocyanins in the extract which helps in the absorption of light. Also, the difference in the absorption spectra could be due to the different colours of the extracts [24]. The absorbance spectra obtained for the extracts indicate that the samples can be used as sensitizers in DSSCs application.…”
Section: Resultsmentioning
confidence: 98%
“…Cosensitizing pigments with a complementary absorption spectra increase the absorption band and are an attractive pathway to enhance the efficiency in DSSCs [124]. Ramirez-Perez et al [104] reported that the predominance of hydroxyl groups on the aromatic skeleton of anthocyanin gives rise to an intense blue color, while a red color is observed in methoxyl functional groups [104]. In brief, lawsone solar cells displayed better performance, showing average efficiencies of 0:311 ± 0:034%, compared to indigo solar cells showing efficiencies of 0:060 ± 0:004%.…”
Section: Computational Studies Of Natural Plant Pigment-based Dsscsmentioning
confidence: 99%
“…Studies on making ecologically acceptable and stable DSSCs using natural dyes and NHC-based iron as sensitizers [8][9][10], copper and other transition metal-based mediators [11,12], and electrolytes based on gels and polymers [13][14][15][16][17] have been published. The steric, structural, and compositional effects of solvent on the efficiency of DSSC have also been investigated electrochemically [15,18].…”
Section: Introductionmentioning
confidence: 99%